Phenazine-quinoxaline organic electrode material and application thereof in preparation of aqueous zinc ion battery

By using phenazine-quinoxaline organic electrode material as the positive electrode material of aqueous zinc ion battery, the problem of insufficient stability of the existing positive electrode material is solved, and high capacity, long life and excellent electrochemical performance are achieved.

CN119528918APending Publication Date: 2025-02-28YANGJIANG JIAOTONG ZHUOYUE NEW ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411723843.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing water-based zinc ion battery positive electrode material is insufficient, resulting in poor cycle life and electrochemical performance.

Method used

The phenazine-quinoxaline organic electrode material is used, which is synthesized by dehydration and condensation reaction of 2,3-diaminophenazine and 2,5-dihydroxy-1,4-benquinole. It has rich C=N groups and π conjugated structures, and is used to prepare the positive electrode of aqueous zinc ion batteries.

Benefits of technology

High reversible specific capacity, long cycle life, better rate performance and wide temperature domain electrochemical performance are achieved, which significantly improves the stability and working performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528918A_ABST
    Figure CN119528918A_ABST
Patent Text Reader

Abstract

The invention provides a phenazine-quinoxaline organic electrode material, and belongs to the technical field of aqueous zinc ion battery electrode materials, and the phenazine-quinoxaline organic electrode material is synthesized from 2, 3-diaminophenazine and 2, 5-dihydroxy-1, 4-benzophenone through a dehydration condensation reaction. The organic electrode material can be used for manufacturing a positive electrode of an aqueous zinc ion battery, and shows relatively high reversible specific capacity, relatively long cycle life, relatively good rate capability and relatively good wide temperature range performance. The invention also provides an application of the phenazine-quinoxaline organic electrode material in preparation of an aqueous zinc ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aqueous zinc ion battery electrode materials, and particularly relates to a phenazine-quinoxaline organic electrode material and application thereof in preparing aqueous zinc ion batteries. Background Art

[0002] To achieve the "dual carbon" goal, it is crucial to choose a safe and environmentally friendly electrochemical energy storage system. Compared with traditional lithium-ion batteries, aqueous ion batteries have more advantages in safety, low cost and environmental sustainability. These advantages make aqueous batteries have considerable prospects in energy storage, new energy vehicles and mobile electronic devices.

[0003] In aqueous ion batteries, zinc metal has a high theoretical specific capacity (820 mAh g -1 ) and low redox potential (-0.76V vs. SHE) stand out. However, the current research on aqueous zinc-ion batteries is still in the exploratory stage, and the main goal is to find high-capacity and stable positive electrode materials. The positive electrode materials used in the past mainly include inorganic compounds such as metal oxides and Prussian blue analogs. These materials are not only costly and polluting, but also prone to layered structure collapse during ion storage, resulting in poor stability. Summary of the invention

[0004] In order to solve the problem of insufficient stability of existing aqueous ion battery positive electrode materials, the present invention provides a phenazine-quinoxaline organic electrode material, which can be used to manufacture the positive electrode of an aqueous zinc ion battery and exhibits higher reversible specific capacity, longer cycle life, better rate performance and better wide temperature range performance.

[0005] The present invention also provides an application of a phenazine-quinoxaline organic electrode material in the preparation of an aqueous zinc ion battery.

[0006] The present invention is achieved through the following technical solutions:

[0007] The present invention provides a phenazine-quinoxaline organic electrode material, and the structural formula of the phenazine-quinoxaline organic electrode material is as follows:

[0008]

[0009] Based on the same inventive concept, the present invention provides a method for preparing a phenazine-quinoxaline organic electrode material. The phenazine-quinoxaline organic electrode material is synthesized from 2,3-diaminophenazine and 2,5-dihydroxy-1,4-benzquinone through a dehydration condensation reaction.

[0010] Furthermore, the preparation method specifically comprises:

[0011] Dissolve 2,3-diaminophenazine and 2,5-dihydroxy-1,4-benzquinol in acetic acid, and then stir and reflux at 90-110° C. for 5-7 hours to obtain a mixture;

[0012] After the mixture is cooled, solid-liquid separation is performed, and the separated solid product is washed several times with acetic acid and deionized water respectively. The washed product is vacuum dried and then Soxhlet extracted with anhydrous ethanol for a period of time. The obtained product is vacuum dried to obtain a phenazine-quinoxaline organic electrode material.

[0013] Furthermore, the molar ratio of the 2,3-diaminophenazine to the 2,5-dihydroxy-1,4-benzquinone is 2:1.

[0014] Further, the mixture is cooled and solid-liquid separated, the solid product obtained by separation is washed several times with acetic acid and deionized water respectively, the washed product is vacuum dried and then extracted with anhydrous ethanol Soxhlet for a period of time, the obtained product is vacuum dried to obtain a phenazine-quinoxaline organic electrode material, specifically comprising:

[0015] After the mixture is cooled, solid-liquid separation is performed, and the separated solid product is washed several times with acetic acid and deionized water respectively. The washed product is vacuum dried and then Soxhlet with anhydrous ethanol for 20 to 28 hours. The obtained product is vacuum dried at 80 to 120° C. for 20 to 28 hours to obtain a phenazine-quinoxaline organic electrode material.

[0016] Among them, the specific process of Soxhlet extraction includes: putting the dried washed product into a filter paper cover and putting it into a Soxhlet extractor; adding anhydrous ethanol into the solvent bottle of the Soxhlet extractor and heating it to reflux at 60-80°C; after 20-28 hours, taking out the filter paper cover and collecting the sample by filtering with ethanol.

[0017] The washed product is then vacuum dried and then Soxhlet extracted with anhydrous ethanol for 20 to 28 hours, specifically comprising:

[0018] The washed product is placed in a filter paper sleeve and placed in a Soxhlet extractor; anhydrous ethanol is added to the solvent bottle of the Soxhlet extractor and heated to reflux at 60-80° C.; after 20-28 hours, the filter paper sleeve is taken out and the sample is collected by filtering with ethanol.

[0019] Based on the same inventive concept, the present invention provides an application of a phenazine-quinoxaline organic electrode material in the preparation of an aqueous zinc ion battery.

[0020] Based on the same inventive concept, the present invention provides an application of a phenazine-quinoxaline organic electrode material in preparing a positive electrode of an aqueous ion battery.

[0021] Based on the same inventive concept, the present invention provides an aqueous zinc ion battery or an aqueous ion battery positive electrode, wherein the aqueous zinc ion battery or the aqueous ion battery positive electrode comprises the above-mentioned phenazine-quinoxaline organic electrode material.

[0022] Based on the same inventive concept, the present invention provides a method for preparing a positive electrode of an aqueous zinc ion battery, the preparation method comprising:

[0023] Dispersing the conductive agent, the binder and the phenazine-quinoxaline organic electrode material in an organic solvent and grinding the mixture to a particle size of 5 to 10 μm to obtain a slurry;

[0024] The slurry is coated on the surface of the current collector, and then vacuum dried and cut to obtain a positive electrode sheet;

[0025] Wherein, the mass ratio of the conductive agent, the binder and the phenazine-quinoxaline organic electrode material is 3:1:6.

[0026] Further, the conductive agent includes Ketjen black;

[0027] The binder includes polyvinylidene fluoride;

[0028] The current collector comprises titanium foil;

[0029] The vacuum drying temperature is 90-110° C., and the vacuum drying time is 10-14 hours.

[0030] Based on the same inventive concept, the present invention provides a method for preparing an aqueous zinc ion battery, the preparation method comprising:

[0031] The positive electrode sheet is used as the positive electrode, the metal zinc foil is used as the negative electrode, a glass fiber separator is used to separate the positive electrode and the negative electrode, and a zinc salt electrolyte is added to assemble an aqueous zinc ion battery.

[0032] Furthermore, in the zinc salt electrolyte, the electrolyte is zinc perchlorate and the solvent is deionized water.

[0033] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0034] 1. The present invention discloses a phenazine-quinoxaline organic electrode material, which is synthesized by a one-step dehydration condensation reaction of 2,3-diaminophenazine and 2,5-dihydroxy-1,4-benzquinone in acetic acid. The organic electrode material is used as a positive electrode material for an aqueous zinc ion battery, wherein the abundant C=N groups can serve as redox active sites and can reversibly store Zn through coordination reactions. 2 +, providing a higher electrochemical specific capacity and achieving excellent stability. At the same time, the π-conjugated structure formed between molecules can effectively inhibit the dissolution of electrode materials, promote electrochemical cycle stability, ensure efficient ion and electron transfer in high and low temperature environments, and ensure rapid electron transfer and ion transport in electrochemical reactions under different temperature environments, thereby achieving excellent electrochemical performance over a wide temperature range.

[0035] 2. The present invention discloses a phenazine-quinoxaline organic electrode material, wherein the abundant C=N active sites and the extended π-π conjugated structure can effectively promote the reversible storage of zinc ions and the transmission of charges, thereby significantly improving the electrochemical specific capacity and cycle stability of the electrode material. Under normal circumstances, the aqueous electrolyte will freeze under low temperature conditions, resulting in a sharp deterioration of the ionic conductivity; and the side reactions will be aggravated under high temperature, thereby aggravating the dissolution of the material, which will cause the battery to fail to work normally. The organic electrode material of the present invention has a symmetrical π conjugated system, which can significantly enhance the conjugation effect between molecules, thereby effectively inhibiting the dissolution of the active material, while promoting electron delocalization, improving the conductivity of the material, and ensuring that it can undergo rapid ion transmission and electron transfer at different temperatures, thereby significantly improving the working performance of the aqueous zinc ion battery under different temperature conditions.

[0036] 3. A phenazine-quinoxaline organic electrode material of the present invention is prepared by a dehydration condensation reaction in an acetic acid solvent using conventional drugs (2,3-diaminophenazine and 2,5-dihydroxy-1,4-benzquinone). The raw materials are cheap and readily available, the synthesis method is simple and fast, and the synthesis yield is high. Compared with inorganic positive electrode materials, the organic electrode material has the advantages of being renewable and environmentally friendly. The organic electrode material contains abundant C=N groups and conjugated structures, so that it can be applied to aqueous zinc ion batteries and exhibits a high cycle specific capacity (300 mAhg -1 ), good rate performance and long cycle life (30,000 cycles), and in the wide temperature range of -50 degrees to +50 degrees, the aqueous zinc ion batteries assembled with phenazine-quinoxaline organic electrode materials can show excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0038] Figure 1 This is a scanned photo of the phenazine-quinoxaline organic electrode material obtained in Example 1 of the present invention.

[0039] Figure 2 This is a Fourier infrared spectrum of the phenazine-quinoxaline organic electrode material obtained in Example 1 of the present invention.

[0040] Figure 3 When the phenazine-quinoxaline organic electrode material obtained in Example 1 of the present invention is used as the positive electrode material of the aqueous zinc ion battery, the scanning rate is 0.2 mVs -1 CV graph of.

[0041] Figure 4 The phenazine-quinoxaline organic electrode material obtained in Example 1 of the present invention is 0.2Ag -1 Electrochemical cycle diagram of room temperature aqueous zinc-ion battery at different current densities.

[0042] Figure 5 The phenazine-quinoxaline organic electrode material obtained in Example 1 of the present invention is 0.2Ag -1 Constant current charge and discharge curve of room temperature aqueous zinc ion battery under current density.

[0043] Figure 6 This is a rate cycling performance diagram of the phenazine-quinoxaline organic electrode material obtained in Example 1 of the present invention when applied to a room temperature aqueous zinc ion battery.

[0044] Figure 7 This is a rate charge and discharge curve diagram of the phenazine-quinoxaline organic electrode material obtained in Example 1 of the present invention when applied to a room temperature aqueous zinc ion battery.

[0045] Figure 8 The phenazine-quinoxaline organic electrode material obtained in Example 1 of the present invention was heated to 10Ag. -1 Electrochemical cycle diagram of room temperature aqueous zinc-ion battery at different current densities.

[0046] Fig. 9 The phenazine-quinoxaline organic electrode material obtained in Example 1 of the present invention was heated to 10Ag. -1 Electrochemical cycle diagram of aqueous zinc-ion battery at different temperatures and current densities.

[0047] Fig.10 The phenazine-quinoxaline organic electrode material obtained in Example 1 of the present invention is prepared on 2Ag -1 Electrochemical cycle diagram of low-temperature (-50℃) aqueous zinc-ion battery under current density. DETAILED DESCRIPTION

[0048] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.

[0049] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0050] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0051] The technical principle of the present invention is as follows:

[0052] The present invention provides a method for preparing a phenazine-quinoxaline organic electrode material, the preparation method specifically comprising:

[0053] S1. dissolving 2,3-diaminophenazine and 2,5-dihydroxy-1,4-benzquinol in acetic acid, and then stirring and refluxing at 90-110° C. for 5-7 hours to obtain a mixture;

[0054] S2. After the mixture is cooled, solid-liquid separation is performed, and the separated solid product is washed several times with acetic acid and deionized water respectively. The washed product is vacuum dried and then Soxhlet extraction is performed with anhydrous ethanol for a period of time. The obtained product is vacuum dried to obtain a phenazine-quinoxaline organic electrode material.

[0055] In the present invention, the stirring reflux reaction temperature is 90-110° C., which has the advantage of controlling the reaction rate while ensuring the safety of the experiment.

[0056] In step S1, the molar ratio of the 2,3-diaminophenazine to the 2,5-dihydroxy-1,4-benzquinone is 2:1.

[0057] In the present invention, the molar ratio of 2,3-diaminophenazine to 2,5-dihydroxy-1,4-benzquinolone is 2:1, which has the advantage that the reactants can react fully.

[0058] Step S2 specifically includes:

[0059] After the mixture is cooled, solid-liquid separation is performed, and the separated solid product is washed several times with acetic acid and deionized water respectively. The washed product is vacuum dried and then Soxhlet with anhydrous ethanol for 20 to 28 hours. The obtained product is vacuum dried at 80 to 120° C. for 20 to 28 hours to obtain a phenazine-quinoxaline organic electrode material.

[0060] The washed product is then vacuum dried and then Soxhlet extracted with anhydrous ethanol for 20 to 28 hours, specifically comprising:

[0061] The washed product is placed in a filter paper sleeve and placed in a Soxhlet extractor; anhydrous ethanol is added to the solvent bottle of the Soxhlet extractor and heated to reflux at 60-80° C.; after 20-28 hours, the filter paper sleeve is taken out and the sample is collected by filtering with ethanol.

[0062] In the present invention, the washed product is vacuum dried and then Soxhlet extracted with anhydrous ethanol for 20 to 28 hours, which is conducive to fully removing impurities.

[0063] Based on the same inventive concept, the present invention provides a method for preparing a positive electrode of an aqueous zinc ion battery, the preparation method comprising:

[0064] The conductive agent, the binder and the phenazine-quinoxaline organic electrode material are dispersed in an organic solvent and then ground to a particle size of 5 to 10 μm to obtain a slurry;

[0065] The slurry is coated on the surface of the current collector, and then vacuum dried and cut to obtain a positive electrode sheet;

[0066] Wherein, the mass ratio of the conductive agent, the binder and the phenazine-quinoxaline organic electrode material is 3:1:6.

[0067] In the present invention, the mass ratio of the conductive agent, the binder and the phenazine-quinoxaline organic electrode material is 3:1:6, which has the advantage of ensuring the loading amount of the active substance and effectively increasing the conductivity of the material, and the advantage of grinding to a particle size of 5 to 10 μm is that the active sites are fully exposed.

[0068] Further, the conductive agent includes Ketjen black;

[0069] The binder includes polyvinylidene fluoride;

[0070] The current collector comprises titanium foil;

[0071] The vacuum drying temperature is 90-110° C., and the vacuum drying time is 10-14 hours.

[0072] Based on the same inventive concept, the present invention provides a method for preparing an aqueous zinc ion battery, the preparation method comprising:

[0073] A positive electrode sheet is used as the positive electrode, a metal zinc foil is used as the negative electrode, a glass fiber separator is used to separate the positive electrode and the negative electrode, and a zinc salt electrolyte is added to assemble an aqueous zinc ion battery.

[0074] Furthermore, in the zinc salt electrolyte, the electrolyte is zinc perchlorate and the solvent is deionized water.

[0075] The following will describe in detail a phenazine-quinoxaline organic electrode material of the present application and its application in the preparation of aqueous zinc ion batteries in combination with examples and experimental data.

[0076] The battery performance tests in the following embodiments all adopt the Xinwei battery testing system and Princeton electrochemical workstation. The low temperature test requires the battery to be placed in a low temperature test box at different temperatures, and the high temperature test requires the battery to be placed in a high temperature test box at 50°C.

[0077] Example 1

[0078] This embodiment provides a method for preparing a phenazine-quinoxaline organic electrode material, and the synthesis route is shown as follows:

[0079]

[0080] Step 1: 842 mg of 2,3-diaminophenazine and 281 mg of 2,5-dihydroxy-1,4-benzquinolone were transferred to a single-necked flask (250 mL) containing 60 mL of acetic acid and stirred evenly. Ultrasonication (to promote dispersion) was performed at room temperature for 30 minutes, and then the reactants were stirred and refluxed at 100° C. for 6 hours.

[0081] Step 2: After the reaction is completed, the reaction system is cooled to room temperature, and the black solid is collected by centrifugation. The solid product is then washed 4 times by centrifugation with acetic acid and deionized water respectively to obtain a solid product, which is vacuum dried at 100°C. The product is then Soxhlet extracted with anhydrous ethanol for 24 hours, and then vacuum dried at 100°C for 24 hours to obtain a black target product, namely phenazine-quinoxaline.

[0082] Example 2

[0083] The phenazine-quinoxaline organic electrode material, Ketjen black and polyvinylidene fluoride (PVDF) obtained in Example 1 were mixed with N-methylpyrrolidone (NMP) solution in a mass ratio of 60:30:10, ground into a well-dispersed slurry (particle size of 5-10 μm) in an agate mortar, and then evenly coated on a titanium foil current collector, and dried at 100°C in vacuum for 12 hours to prepare a working electrode. The working electrode was used as the positive electrode, the metal zinc foil was used as the negative electrode, the glass fiber membrane was used as the diaphragm, and a 2M zinc perchlorate solution was used as the electrolyte (configuration) to assemble a 2032 button cell. The test voltage range was 0.3V-1.5V relative to Zn / Zn 2+ .

[0084] Figure 1 This is a scanned photo of the phenazine-quinoxaline organic electrode material obtained in the example of the present invention. It can be clearly seen from the picture that the compound is irregularly spherical and aggregated.

[0085] Figure 2 This is the Fourier infrared spectrum of the phenazine-quinoxaline organic electrode material obtained in the present invention. The phenazine-quinoxaline compound has a peak at 1231 cm -1 and 1506cm-1 The characteristic peaks at correspond to CN and C=N bonds, respectively, which indicates the formation of the compound.

[0086] Figure 3 The 2032 button cell prepared in Example 2 of the present invention is 0.2mV s -1 The room temperature cyclic voltammetry curve at the scanning rate. The battery has two pairs of redox peaks, located at 1.02 / 0.91V and 0.62 / 0.50V (relative to Zn / Zn 2 + ).

[0087] Figure 4 The 2032 button cell prepared in Example 2 of the present invention is 0.2Ag -1 Room temperature electrochemical cycle diagram under current density. It can be seen from the figure that at 0.2Ag -1 At a current density of 1.5 volts, its first cycle coulombic efficiency is as high as 90%, and it shows 100% coulombic efficiency in subsequent cycles. Its maximum specific capacity is 300 mAh g -1 , after 500 cycles, the capacity retention rate is as high as 90%. It can be concluded that the phenazine-quinoxaline organic electrode material has a high capacity and excellent cycle stability.

[0088] Figure 5 The 2032 button cell prepared in Example 2 of the present invention is 0.2Ag -1 Room temperature constant current charge-discharge curve under current density. Two pairs of inclined platforms can be observed in the charge-discharge curve, corresponding to the redox peaks in the cyclic voltammetry curve of the material. After 500 cycles, it can still maintain 270mAhg -1 The high specific capacity and voltage platform demonstrate the good electrochemical stability of the material.

[0089] Figure 6 The room temperature rate performance diagram of the 2032 button battery prepared in Example 2 of the present invention at different current densities is shown. The battery has a room temperature rate performance of 0.2, 0.5, 1.0, 2.0, 3.0, 5.0, 8.0, 10, and 20 Ag. -1 At current densities of 300, 260, 240, 225, 215, 205, 189, 180 and 163 mAh g -1 The high discharge capacity, when the current density returns to the initial 0.2A -1 When the discharge capacity can still return to 290mAhg -1 , proving that the material not only has excellent rate performance, but also maintains excellent reversibility.

[0090] Figure 7The room temperature charge and discharge curves of the 2032 button cell prepared in Example 2 of the present invention at different current densities are shown in the figure. From the figure, it can be seen that at different current densities, the trend and platform of the charge and discharge curves remain consistent, proving the excellent rate performance of the phenazine-quinoxaline positive electrode.

[0091] Figure 8 The 2032 button cell prepared in Example 2 of the present invention is 10Ag -1 Room temperature long cycle performance diagram under current density. It can be seen from the figure that at 10Ag -1 At a current density of , the battery can stably cycle 30,000 times with a capacity retention rate of 75%, demonstrating the excellent long-cycle performance of the phenazine-quinoxaline cathode.

[0092] Fig. 9 The electrochemical cycle diagram of the 2032 button battery prepared in Example 2 of the present invention at different temperatures. The battery can obtain 310, 300, 266, 215 and 173 mAhg at temperatures of 50, 25, 0, -25 and -50 °C, respectively. -1 The high discharge capacity proves that the material can exhibit high electrochemical performance under different temperature environments.

[0093] Fig.10 The 2032 button cell prepared in Example 2 of the present invention is 2Ag -1 Low temperature (-50°C) electrochemical cycle diagram under current density. The battery was placed in a -50°C low temperature test chamber for testing after 5 cycles at room temperature. At low temperature (-50°C), the battery also exhibited excellent electrochemical specific capacity and excellent zinc storage performance. -1 At a current density of 1.3 %, the reversible specific capacity is stable at 113 mAh g after 10,000 cycles. -1 .

[0094] In summary, the phenazine-quinoxaline organic electrode material prepared in the present invention exhibits excellent electrochemical performance and stability when applied to positive electrode materials of aqueous zinc ion batteries.

[0095] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.

[0096] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0097] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A phenazine-quinoxaline organic electrode material, characterized in that: The structural formula of the phenazine-quinoxaline organic electrode material is as follows:

2. The method for preparing a phenazine-quinoxaline organic electrode material according to claim 1, characterized in that: The phenazine-quinoxaline organic electrode material is synthesized from 2,3-diaminophenazine and 2,5-dihydroxy-1,4-benzquinone through a dehydration condensation reaction.

3. The method for preparing a phenazine-quinoxaline organic electrode material according to claim 2, characterized in that: The preparation method specifically comprises: Dissolve 2,3-diaminophenazine and 2,5-dihydroxy-1,4-benzquinol in acetic acid, and then stir and reflux at 90-110° C. for 5-7 hours to obtain a mixture; After the mixture is cooled, solid-liquid separation is performed, and the separated solid product is washed several times with acetic acid and deionized water respectively. The washed product is vacuum dried and then Soxhlet extracted with anhydrous ethanol for a period of time. The obtained product is vacuum dried to obtain a phenazine-quinoxaline organic electrode material.

4. The method for preparing a phenazine-quinoxaline organic electrode material according to claim 3, characterized in that: The molar ratio of the 2,3-diaminophenazine to the 2,5-dihydroxy-1,4-benzquinone is 2:

1.

5. The method for preparing a phenazine-quinoxaline organic electrode material according to claim 3, characterized in that: After the mixture is cooled, solid-liquid separation is performed, and the solid product obtained by separation is washed several times with acetic acid and deionized water respectively. The washed product is vacuum dried and then extracted with anhydrous ethanol Soxhlet for a period of time. The obtained product is vacuum dried to obtain a phenazine-quinoxaline organic electrode material, which specifically includes: After the mixture is cooled, solid-liquid separation is performed, and the separated solid product is washed several times with acetic acid and deionized water respectively. The washed product is vacuum dried and then extracted with anhydrous ethanol Soxhlet for 20 to 28 hours. The obtained product is vacuum dried at 80 to 120° C. for 20 to 28 hours to obtain a phenazine-quinoxaline organic electrode material.

6. Use of a phenazine-quinoxaline organic electrode material as claimed in claim 1 in the preparation of an aqueous zinc ion battery.

7. Use of a phenazine-quinoxaline organic electrode material as claimed in claim 1 in preparing a positive electrode of an aqueous ion battery.

8. An aqueous zinc ion battery or an aqueous ion battery positive electrode, characterized in that: The positive electrode of the aqueous zinc ion battery or aqueous ion battery comprises the phenazine-quinoxaline organic electrode material according to claim 1.

9. A method for preparing a positive electrode of an aqueous zinc ion battery, characterized in that: The preparation method comprises: Dispersing the conductive agent, the binder and the phenazine-quinoxaline organic electrode material according to claim 1 in an organic solvent and grinding the mixture to a particle size of 5 to 10 μm to obtain a slurry; The slurry is coated on the surface of the current collector, and then vacuum dried and cut to obtain a positive electrode sheet; Wherein, the mass ratio of the conductive agent, the binder and the phenazine-quinoxaline organic electrode material is 3:1:6; The conductive agent includes Ketjen black; The binder includes polyvinylidene fluoride; The current collector comprises titanium foil; The vacuum drying temperature is 90-110° C., and the vacuum drying time is 10-14 hours.

10. A method for preparing an aqueous zinc ion battery, characterized in that: The preparation method comprises: The positive electrode sheet prepared according to claim 9 or 10 is used as the positive electrode, the metal zinc foil is used as the negative electrode, the positive electrode and the negative electrode are separated by a glass fiber separator, a zinc salt electrolyte is added, and an aqueous zinc ion battery is assembled.

Citation Information

Patent Citations

  • Aqueous all-organic secondary battery based on azine compounds with multiple oxidation states

    CN113328092A

  • Organic positive electrode of aqueous zinc ion battery and battery

    CN117219767A

  • Preparation method and application of desalted organic matter containing polyphenazine linear structure

    CN118005642A

  • Novel method for the preparation of derivatives of dihydrotetraazapentacenes, products such as obtained, and uses thereof

    WO2009083532A2

  • Novel phenazine-based compounds

    WO2021165542A1

Cited By

  • Pyridyl phenazine aqueous positive electrode material and preparation method and application thereof

    CN121318972A